A new conceptual model for quantifying transboundary contribution of atmospheric pollutants in the East Asian Pacific rim region. (March 2016) - Lai, I-Chien; Lee, Chon-Lin; Huang, Hu-Ching
Abstract: Transboundary transport of air pollution is a serious environmental concern as pollutant affects both human health and the environment. Many numerical approaches have been utilized to quantify the amounts of pollutants transported to receptor regions, based on emission inventories from possible source regions. However, sparse temporal–spatial observational data and uncertainty in emission inventories might make the transboundary transport contribution difficult to estimate. This study presents a conceptual quantitative approach that uses transport pathway classification in combination with curve fitting models to simulate an air pollutant concentration baseline for pollution background concentrations. This approach is used to investigate the transboundary transport contribution of atmospheric pollutants to a metropolitan area in the East Asian Pacific rim region. Trajectory analysis categorized pollution sources for the study area into three regions: East Asia, Southeast Asia, and Taiwan cities. The occurrence frequency and transboundary contribution results suggest the predominant source region is the East Asian continent. This study also presents an application to evaluate heavy pollution cases for health concerns. This new baseline construction model provides a useful tool for the study of the contribution of transboundary pollution delivered to receptors, especially for areas deficient in emission inventories and regulatory monitoring data for harmful air pollutants. Highlights: A conceptual transboundary pollutant contribution quantitative method is proposed. Predominant source region: East Asia contributed around 39.5–55.6% pollutants. In heavy pollution cases, more than 50% pollutants were from transboundary transport. High winter PAH concentration was attributed to heating activities in East Asia.